2002
DOI: 10.1142/s0218810402001084
|View full text |Cite
|
Sign up to set email alerts
|

Interposition Arthroplasty for Osteoarthritis of Trapezio Metacarpal Joint: Results of a Modified Incision and Technique of Interposing With Early Mobilisation

Abstract: Sixty flexor carpi radialis (FCR) tendon interposition arthroplasties were done using a modified incision from Froimson's approach for osteoarthritis (OA) of thumb carpo metacarpal joint (CMCJ) The tendon was made to resemble an anchovy fillet to preserve pillar length (average 7.5 mm). There was no incidence of injury to the superficial branch of the radial nerve. Graded mobilisation was commenced at two weeks. Our average follow-up for five and a half years shows good results, viz. pain relief (100%), power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…27 Maqsood et al reported data on LRTI using FCR tendon interposition and mobilizing patients at 2 weeks. 29 At 5.5 years their series of 60 patients had normal mobility and no cases of CRPS. De Smet et al reported data on a cohort of patients undergoing trapeziectomy and/or LRTI who mobilized within a week.…”
Section: Discussionmentioning
confidence: 92%
“…27 Maqsood et al reported data on LRTI using FCR tendon interposition and mobilizing patients at 2 weeks. 29 At 5.5 years their series of 60 patients had normal mobility and no cases of CRPS. De Smet et al reported data on a cohort of patients undergoing trapeziectomy and/or LRTI who mobilized within a week.…”
Section: Discussionmentioning
confidence: 92%
“…Women have a greater predilection for degenerative arthritis at this joint than men. 120 Because many daily activities are markedly affected by the pain of arthritic changes at the CMC joint, surgical intervention is common. Surgical management of arthritis in the distal upper extremity is most frequently provided at this joint.…”
Section: Thumb Carpometacarpal Surgerymentioning
confidence: 99%
“…However, subluxation correlated with poor results in this study, leading the authors to conclude that ligament reconstruction was worthwhile. Maqsood also reported excellent results after T+IA (Table 4) (Level IV Evidence) 13…”
Section: Evidence On Surgical Treatment Planmentioning
confidence: 88%
“…Results are very predictable with this method. Maqsood reported on a series of T+LRTI patients mobilized early (2 weeks) (Level IV Evidence) 13. He felt this was important to reduce the incidence of stiffness and complex regional pain syndrome (CRPS).…”
Section: Evidence On Postoperative Outcomesmentioning
confidence: 99%